Microvascular and Macrovascular Abnormalities and Cognitive and Physical Function in Older Adults: Cardiovascular Health Study. Issue 9 (4th September 2015) - Kim, Dae Hyun; Grodstein, Francine; Newman, Anne B.; Chaves, Paulo H. M.; Odden, Michelle C.; Klein, Ronald; Sarnak, Mark J.; Lipsitz, Lewis A.
<x xml:space="preserve">Abstract</x> Objectives To evaluate and compare the associations between microvascular and macrovascular abnormalities and cognitive and physical function Design Cross‐sectional analysis of the Cardiovascular Health Study (1998–1999). Setting Community. Participants Individuals with available data on three or more of five microvascular abnormalities (brain, retina, kidney) and three or more of six macrovascular abnormalities (brain, carotid artery, heart, peripheral artery) (N = 2, 452; mean age 79.5). Measurements Standardized composite scores derived from three cognitive tests (Modified Mini‐Mental State Examination, Digit‐Symbol Substitution Test, Trail‐Making Test (TMT)) and three physical tests (gait speed, grip strength, 5‐time sit to stand) Results Participants with high microvascular and macrovascular burden had worse cognitive (mean score difference = −0.30, 95% confidence interval (CI) = −0.37 to −0.24) and physical (mean score difference = −0.32, 95% CI = −0.38 to −0.26) function than those with low microvascular and macrovascular burden. Individuals with high microvascular burden alone had similarly lower scores than those with high macrovascular burden alone (cognitive function: −0.16, 95% CI = −0.24 to −0.08 vs −0.13, 95% CI = −0.20 to −0.06; physical function: −0.15, 95% CI = −0.22 to −0.08 vs −0.12, 95% CI = −0.18 to −0.06). Psychomotor speed and working memory, assessed using the TMT, were only impaired in the presence of high microvascular burden. Of the 11 vascular abnormalities considered, white matter hyperintensity, cystatin C–based glomerular filtration rate, large brain infarct, and ankle–arm index were independently associated with cognitive and physical function. Conclusion Microvascular and macrovascular abnormalities assessed using noninvasive tests of the brain, kidney, and peripheral artery were independently associated with poor cognitive and physical function in older adults. Future research should evaluate the usefulness of these tests in prognostication.